Penerapan Edukasi Pencegahan Risiko Jatuh Terhadap Peningkatan Pengetahuan Dan Persepsi Pasien Dalam Mencegah Jatuh Di Ruang Rawat Inap Rumah Sakit X - Rani Mutrika; Serri Hutahaean (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: This study was conducted to determine the effectiveness of the implementing fall risk prevention education in increasing patient knowledge and perception of risk of falling.Methods: This study uses a quasi-experimental pre-post test design without a control group. The sample of this study amounted to 30 patients in the inpatient room of Hospital X.Results: The results showed that after being given an educational intervention, it showed that 25 of 30 patients (86%) experienced an increase in knowledge of the fall risk and an increase in score of 91%. The results of the paired t-test analysis showed a significant increase (p = 0.000) between the pre-test and post-test.Conclusion: It can be indicated that there is effectiveness of fall risk prevention education in increasing the patient's knowledge and perception of the risk of falling.